Analysis of Sri-Kehati Stock Performance in The Period Before and During Covid-19 Using The Sharpe, Treynor, and Jensen Methods - Aria Nindita Wulansari; Totok Sugiharto (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2024)
This research aims to compare the performance of the SRI-KEHATI index stocks before and during the COVID-19 period using the Sharpe Ratio, Treynor Ratio, and Jensen's Alpha. A quantitative method with a descriptive approach was used in this study, utilizing secondary data. Sample data selection employed a non-probability method with a purposive sampling technique from a single population. Statistical tests were then conducted using paired sample t-test to examine whether there is a difference in portfolio performance among the stocks in the SRI-KEHATI index between the periods before and during the COVID-19 pandemic using the Sharpe, Treynor, and Jensen methods. The results of this research indicate that there was a notable contrast between the periods before and during the COVID-19 pandemic when utilizing the Sharpe Ratio and Treynor Ratio measurement methods. However, this discrepancy was not observed when employing the Jensen Method, as there was no significant difference detected between the two periods.